2019
DOI: 10.29392/joghr.3.e2019085
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with severe postpartum haemorrhage: systematic review using Bradford Hill’s causality framework

Abstract: Back Background ground Severe postpartum haemorrhage (S-PPH) is the leading cause of maternal death worldwide. We aimed to provide an up-to-date summary about S-PPH determinants. Methods Methods We performed a systematic review following the Preferred Reporting Items for Systematic reviews and Meta-analysis (PRISMA) guidelines. We searched the terms "risk factor", "determinant", "post-partum haemorrhage" and "severe", within Web of Science, Scopus, Science Direct, Medline, Cochrane, and Clinical Trials.gov dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…We found that women with history of PPH were more likely to experience PPH than their counterparts 16 indicating the importance of counseling women about recurrence of PPH in subsequent pregnancies. Congruent with previous findings, PPH was more likely among women with no ANC follow up.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…We found that women with history of PPH were more likely to experience PPH than their counterparts 16 indicating the importance of counseling women about recurrence of PPH in subsequent pregnancies. Congruent with previous findings, PPH was more likely among women with no ANC follow up.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, magnitude of PPH may vary between and within geographical regions as a result of variation in diagnosis, quality of documentation or due to subjective estimation of blood loss). 17,[23][24][25][26] We found that women with history of PPH were more likely to experience PPH than their counterparts 16 indicating the importance of counseling women about recurrence of PPH in subsequent pregnancies. Congruent with previous findings, PPH was more likely among women with no ANC follow up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations